2015
DOI: 10.1186/s12906-015-0915-x
|View full text |Cite
|
Sign up to set email alerts
|

Aegle marmelos fruit extract attenuates Helicobacter pylori Lipopolysaccharide induced oxidative stress in Sprague Dawley rats

Abstract: BackgroundBael (Aegle marmelos (L.) Corr.) has been widely used in indigenous systems of Indian medicine to exploit its medicinal properties including astringent, antidiarrheal, antidysenteric, demulcent, antipyretic, antiulcer, anti-inflammatory and anti cancer activities. The present study aims to evaluate the antioxidative and antiulcer effect of methanolic extract of unripe fruit of Aegle marmelos (MEAM) against Helicobacter pylori-Lipopolysaccharide (HP-LPS) induced gastric ulcer in Sprague Dawley (SD) ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 63 publications
0
46
0
Order By: Relevance
“…Fruit methanol extract Sprague Dawley rats Prevented reduction of antioxidants Inhibited lipid peroxidation (Ramakrishna et al, 2015).…”
Section: Aegle Marmelosmentioning
confidence: 99%
See 1 more Smart Citation
“…Fruit methanol extract Sprague Dawley rats Prevented reduction of antioxidants Inhibited lipid peroxidation (Ramakrishna et al, 2015).…”
Section: Aegle Marmelosmentioning
confidence: 99%
“…Moreover, Achillea millefolium, Berberis aristata, Coriandrum sativum, Foeniculum vulgare, Matricaria chamomilla, and Prunus domestica have been illustrated to significantly inhibit the ROS generation in H. pylori-infected cells (Zaidi et al, 2012). Ramakrishna, Savithri, Kist, & Devaraj (2015) tested the activities of the methanol extract of Aegle marmelos fruit on attenuating H. pylori lipopolysaccharide-induced oxidative stress in Sprague-Dawley rats. It was concluded that the extract ameliorated the gastric ulcer, significantly inhibited the increase of gastric secretory parameters in ulcerated rats, prevented the reduction of enzymatic and nonenzymatic antioxidants after induction, and inhibited lipid peroxidation.…”
Section: Anti-oxidative Stress Activitymentioning
confidence: 99%
“…These limitations of current therapy urge for the development of plant‐based therapeutic intervention. It has been reported that A. marmelos fruit extract exerts anti‐ulcerative effect through its antioxidant activity in experimentally induced gastric ulcer model (Ramakrishna, Savithri, Kist, & Devaraj, 2015). Furthermore, the ulcers developed by cold restraint stress in rats and guinea pigs have been effectively treated by pyranocoumarin treatment (Maity, Hansda, Bandyopadhyay, & Mishra, 2009).…”
Section: Baelmentioning
confidence: 99%
“…Furthermore, the ulcers developed by cold restraint stress in rats and guinea pigs have been effectively treated by pyranocoumarin treatment (Maity, Hansda, Bandyopadhyay, & Mishra, 2009). Studies have shown that rats pretreated with immature A. marmelos fruit extract reduced gastric ulcer induced by absolute ethanol (Ramakrishna et al., 2015).…”
Section: Baelmentioning
confidence: 99%
“…Oral administration of methanolic extract of Aegle marmelos fruit reduced the gastric ulcer compared to standard drug sucralfate and significantly inhibited the increase in gastric secretory parameters in ulcerated rats It was concluded that antioxidant properties of Aegle marmelos contributes to the gastroprotective effect in Helicobacter pylori-Lipopolysaccharide induced gastric ulcer model. 39 G. Vimala & F. Gricilda Shoba (2014) discussed some medicinal plants which are mentioned in Ayurveda and also in modern science for the treatment or prevention of peptic ulcer. 8 Pushpendra K. Patel et al (2012) summarizes the pharmacological activity of Aegle marmelos based on scientific information.…”
Section: Antibacterial Activity Of Aegle Marmelosmentioning
confidence: 99%